Management Of Asesmen Nasional Berbasis Komputer (ANBK) In SMP Negeri 23 Krui Regional School 3T (Frontier, Outermost Left Behind) - Sadita, Sadita; Rini, Riswanti; Rini, Hasan; yah, Sowi (CV. Inara, 2022)
The purpose of this study was to analyze and describe the planning, organization, implementation and supervision of the Asesmen Nasional Berbasis Komputer (ANBK) at SMP Negeri 23 Krui, 3T regional schools (frontier, outermost and left behind). This research uses a qualitative approach with a case study research design. Data collection techniques using interviews, observation and document study. Sources of data from this study amounted to 8 people with key informants the principal, and the deputy head informant, 2 teachers, 2 students, school committees and school operators. Data analysis techniques were carried out by collecting data, reducing data, presenting data, and drawing conclusions. The research results show that: 1). Planning is done by containing 6 (six) elements, namely: the what, the why, the where, the when, the who, and the how. 2). The organization is carried out by establishing the ANBK committee, facilities and infrastructure in ANBK activities, and dividing the time for ANBK activities. 3). Implementation is carried out with motivation, leadership, staff arrangement and coordination. 4). Supervision is carried out to determine the supporting factors, inhibiting factors, efficiency, effectiveness and stakeholders.